A Feasibility study on SPRIA-Kit - Javier, Jude K.; Manabat, Ronald Erwin F.; Sulangi, Jaynel R.; Vasquez, Jennifer R. (College of Engineering, 1996)
The SPRIA-KIT to be manufactured by Materia Medica, Inc. is a product of very high standards. It is 99.9% reliable in its results, efficient, easy to use, allows less handling , renders good services and its sold at lower price as compared to its competitors. As determined by the market study, the project is feasible with an annual demand growth increase of 3.13% from an actual demand of 539,004 units in 1997. These demand figures were garnered from its potential target market namely the hospitals and other institutions who performs HBV testing. The potential market share was also projected at a conservative figure of 7.5%. The technical aspect of the project shows promising results as well. Raw materials and equipment are sourced locally which translates and harmonizes good relationship with suppliers. Definite manufacturing location at C.B. Vitug, 559 E.C. Reyes St., Ermita, Manila was established alongside meeting minimal production labor needs of five (5) workers. The project clearly shows that the venture will be able to payback all its expenditures of P 13,839,706.86 on the first year alone. Financially, the company determined the Development Bank of the Philippines as the most appealing banking institution that will be able to service the total monetary needs of the company at 8 million which will allow low owner's equity as well. The project provides high allowance in the projects ability to service its debt obligations within the 5 year period , projecting the payback period at 1.3755 years. This figure is suported by the fact that the company still generates a net income afte tax of P 4,554,050.98 during the first year of its operation. Also, the financial analysis illusrates an attractive NPV (P 9.8M) and IRR (65.80%) indicating a profitable position of the project. The social profitability analysis, together with the organization and management study, exemplifies the unparalleled benefits the product will bring to the society. Human resources is at a minimum which means savings to the company and effective employment to the community. Evaluating all the data gathered, the SPRIA-kit product by Materia Medica, Inc. is FEASIBLE. An appropriate investment proposal can therefore be prepared to further pursue the project.